Predation on herring, Clupea harengus, by minke whales, Balaenoptera acutorostrata, in the Barents Sea - Lindstrøm, Ulf; Haug, Tore; Røttingen, Ingolf (ICES Journal of Marine Science, 2002)
Using results from annual studies in 1992–1999 in the Barents Sea, the dynamics of Northeast Atlantic minke whale ( Balaenoptera acutorostrata ) predation upon immature Norwegian spring spawning herring ( Clupea harengus ) are assessed. Herring spawn along the western coast of Norway, and the larvae are transported northwards to coastal areas of the southern Barents Sea where they spend their first two to four years. The abundance of immature herring year classes in the Barents Sea has been highly variable. One or a few strong year classes are usually followed by several poor year classes. In the study period, there were two particularly strong year classes (1991 and 1992). By 1996, these year classes had migrated out of the Barents Sea, and the abundance of young herring consequently decreased. In the period 1992–1999, the mean annual consumption of immature herring by minke whales in the southern Barents Sea varied considerably (640–118 000 t). The major part of the consumed herring belonged to the strong 1991 and 1992 year classes and there was a substantial reduction in the dietary importance of herring to whales after 1995, when a major part of both the 1991 and 1992 year classes migrated out of the Barents Sea. In 1992–1997, minke whales may have consumed 230 000 and 74 000 t, corresponding to 14.6 and 2.8×109 individuals of the herring year classes of 1991 and 1992, respectively. The dietary importance of herring to whales appeared to increase in a non-linear relation with herring abundance.